Comparative analysis of selection and seeding terms in different systematic languages - Khamidov, Mirmukhsin (The Lingua Spectrum, 2025)
This article presents a comparative analysis of key terms in the fields of plant breeding and seed production in Uzbek, Russian, English, and German. The research contributes to multilingual terminology development, agricultural translation, and interdisciplinary linguistic studies.